Validity, functional impairment and complications related to Internet gaming disorder in the DSM-5 and gaming disorder in the ICD-11. (July 2020) - Ko, Chih-Hung; Lin, Huang-Chi; Lin, Pai-Cheng; Yen, Ju-Yu
Background: Many concerns have been raised regarding the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) criteria for Internet gaming disorder and International Classification of Diseases, 11th Revision (ICD-11) criteria for gaming disorder. Aims: In this study, we demonstrated the diagnostic validity of each criterion for Internet gaming disorder in the DSM-5 in terms of their intensity and frequency thresholds and evaluated functional impairments, unhealthy behaviors and complications among adults with Internet gaming disorder and gaming disorder. Methods: We recruited 69 subjects with Internet gaming disorder, 69 regular gamers and 69 controls without regular gaming based on diagnostic interviewing conducted by a psychiatrist according to the DSM-5 Internet gaming disorder criteria. Results: Except for the 'deceiving' and 'escapism' criteria, all criteria for Internet gaming disorder had a diagnostic accuracy ranging from 84.7% to 93.5% in differentiating between adults with Internet gaming disorder and regular gamers. A total of 44 participants with Internet gaming disorder (63.8%) fulfilled the gaming disorder criteria. In addition, 89% and 100% of the Internet gaming disorder and gaming disorder groups, respectively, had academic, occupational or social functional impairment. Both the Internet gaming disorder and gaming disorder groups had higher rates of delayed sleep phase syndrome and insomnia. The gaming disorder group also had a higher obesity proportion. Conclusion: The 'deceiving' and 'escapism' criteria had relatively lower diagnostic accuracy. Both the Internet gaming disorder and gaming disorder groups demonstrated functional impairments and unhealthy behaviors. They also exhibited complications, such as obesity and sleep disorders. These results support the utility of the DSM-5 Internet gaming disorder and ICD-11 gaming disorder criteria in identifying individuals who need treatment for both gaming addiction symptoms and complications resulting from the addiction.